The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3390/agriculture6020023
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Secondary Metabolites in Response to Drought Stress of Rice (Oryza sativa L.)

Abstract: Abstract:In this study, responses of rice under drought stress correlating with changes in chemical compositions were examined. Among 20 studied rice cultivars, Q8 was the most tolerant, whereas Q2 was the most susceptible to drought. Total phenols, total flavonoids, and antioxidant activities, and their accumulation in water deficit conditions were proportional to drought resistance levels of rice. In detail, total phenols and total flavonoids in Q8 (65.3 mg gallic acid equivalent (GAE) and 37.8 mg rutin equi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
49
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(65 citation statements)
references
References 41 publications
10
49
2
Order By: Relevance
“…The metabolic changes in level of foliar phenolics and increased PAL activity during cold acclimation in androgenic forms of Festulolium were observed in frost-tolerant and snow mould-tolerant (cross-tolerant) genotypes (Pociecha et al 2008). A rise of the cell wallbound phenolics concentration was also correlated with the productivity of triticale (Hura et al 2012) and rice (Quan et al 2016) under soil drought. Furthermore, during the microscopic analysis, the cell wall-phenolics accumulated in sites of M. nivale invasion in winter triticale , Lolium perenne (Dubas et al 2010) and winter rye (Żur et al 2011) seedlings.…”
Section: Discussionmentioning
confidence: 88%
“…The metabolic changes in level of foliar phenolics and increased PAL activity during cold acclimation in androgenic forms of Festulolium were observed in frost-tolerant and snow mould-tolerant (cross-tolerant) genotypes (Pociecha et al 2008). A rise of the cell wallbound phenolics concentration was also correlated with the productivity of triticale (Hura et al 2012) and rice (Quan et al 2016) under soil drought. Furthermore, during the microscopic analysis, the cell wall-phenolics accumulated in sites of M. nivale invasion in winter triticale , Lolium perenne (Dubas et al 2010) and winter rye (Żur et al 2011) seedlings.…”
Section: Discussionmentioning
confidence: 88%
“…It was estimated that 50% of the rice production can be affected by drought [25]. Thus, there have been many studies conducted with attempts to breed rice cultivars tolerant to drought [26], as well as proper water use in rice production against drought [6]. In addition, a number of new rice varieties have been bred and released yearly with higher yield potential and stronger resistance to abiotic and biotic stresses.…”
Section: Introductionmentioning
confidence: 99%
“…Phenolics are not the main factor to assist rice to escape from flooding condition or shoot elongation, but the high accumulation of such secondary metabolite partly protects plant cells from physical injuries during exposure to stress conditions, especially submergence. For instance, Quan et al [22] reported the presence of only-hydroxybenzoic acid in the tolerant rice variety after drought stress treatment.…”
Section: Anaerobic Flooding Germination and Phenolic Compounds Of Ricementioning
confidence: 99%